Gagalnya Eksplorasi Panas Bumi Di Baturaden Dalam PerspektifKriminologi Hijau - Arif Awaludin; Teguh Anindito; Doni Adi Supriyo (Wijayakusuma Law Review, 2023)
Geothermal is a renewable energy source that will contribute to the energy mix in Indonesia. Geothermal explorationis often carried out in forest areas in Indonesia. Many problems arise. The failure of geothermal exploration inBaturaden which has been carried out since 2017 has left two unproductive wells. Land clearing, deforestation andgroundwater pollution are part of the damage caused. A Green Criminology approach is needed to uncover variouspotential crimes that arise and how to overcome them. Qualitative analysis is used to help reveal in detail thepotential crimes that occur. A comprehensive policy is needed to overcome environmental crimes related togeothermal exploration in Indonesia. The existence of Law concerning Environmental Protection and ManagementNumber 32 of 2009, Law Number 21 of 2014 concerning Geothermal Energy and Law Number 18 of 2013concerning Prevention and Eradication of Forest Destruction need to be harmonized so that environmental lawenforcement policies become more effective and efficient